Substitution of chayote, dragon fruit peel, and kepok banana peel on nutrient content and sensory of Vegetable Leather as high fiber snack - Septia Rosdyaningrum; Laras Sitoayu; Putri Ronitawati; Vitria Melani; Reza Fadhilla (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
Consumption of vegetables and fruit in school-age children, which is still less than the recommended five servings/day in 2018, can increase the risk of nutritional problems in children due to low fiber consumption, leading to obesity. High-fiber snacks made from local food can be a solution. However, the availability is still limited. This research aims to develop snack products from chayote, dragon fruit peel, and Kepok banana peel. This quasi-experimental study was conducted from April 2021 to August 2022 at Saraswanti Indo Genetech Chemistry Laboratorium in Bogor. The sample consists of moderately trained panelists, as many as 30 people. There were four concentration formulations of chayote, dragon fruit peel, and Kepok banana peel. Data were analyzed using One Way Anova and followed by Duncan Multiple Range Test (DMRT). The result shows significant differences in color (p= 0,000), taste (p= 0,000), texture (p= 0,000), and overall preference level between formulations (p= 0,002). The selected F2 contains a water content of 18,25%, ash content of 3,12%, protein of 2,82%, fat of 0,28%, carbohydrates of 75,53%, dietary fiber of 10,48 %, and a total plate count of 30 colonies/g. In conclusion, the F2 tends to be more liked by the panelists and can be considered high in fiber.